2015
DOI: 10.1088/0026-1394/52/2/301
|View full text |Cite
|
Sign up to set email alerts
|

1 × 10−16frequency transfer by GPS PPP with integer ambiguity resolution

Abstract: For many years, the time community has been using the precise point positioning (PPP) technique which uses GPS phase and code observations to compute time and frequency links. However, progress in atomic clocks implies that the performance of PPP frequency comparisons is a limiting factor in comparing the best frequency standards. We show that a PPP technique where the integer nature of phase ambiguities is preserved consitutes significant improvement of the classical use of floating ambiguities. We demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
94
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(96 citation statements)
references
References 20 publications
2
94
0
Order By: Relevance
“…Since the two receivers are connected to the same maser, this part of the setup constitutes a common clock very-short-baseline configuration, which is analyzed using the NRCan PPP software. Similar investigations have been performed in [23] (slide 13) and [24]. Such a comparison is not affected by the frequency instability of the masers, the effects of signal propagation through the ionosphere and instabilities of the IGS time.…”
Section: Signal Validation and Uncertainty Contributionssupporting
confidence: 54%
“…Since the two receivers are connected to the same maser, this part of the setup constitutes a common clock very-short-baseline configuration, which is analyzed using the NRCan PPP software. Similar investigations have been performed in [23] (slide 13) and [24]. Such a comparison is not affected by the frequency instability of the masers, the effects of signal propagation through the ionosphere and instabilities of the IGS time.…”
Section: Signal Validation and Uncertainty Contributionssupporting
confidence: 54%
“…To see more details about the relative time change between two receivers, we show the time difference between two receivers in this section. The time difference between two receivers sharing the same reference time is also called "common-clock difference (CCD)" [21][22][23]. In principle, the time difference between two NIST receivers should be a constant.…”
Section: Long-term Uncertainty In Gps Cp Time Transfermentioning
confidence: 99%
“…Compared with GNSS code-only techniques, such as CV and All-in-View (AV) [9], better short-term stability in time transfer can be achieve with PPP. The present typical uncertainty of PPP-based frequency comparison is about 1 × 10 −15 at 1-day average and about 1 × 10 −16 at 30-day average, where corresponding to type A uncertainty of 0.3 ns for time-links in the Bureau International des Poids et Mesures (BIPM) Circular T. Moreover, the integer-PPP (IPPP) technique implemented by CNES (Centre National d'Etudes Spatiales) was first applied to perform frequency transfer [10]. The results demonstrated that the IPPP technique allowed frequency comparison with 1 × 10 −16 accuracy in several days and could be readily operated with existing products.…”
Section: Introductionmentioning
confidence: 99%